Inspection Planning of Subsea Pipeline Using Risk-Based Inspection - Adelia, Ni Luh Triska; Munir, Badrul; Soedarsono, Johny Wahyuadi (Journal of Materials Exploration and Findings, 2024)
Pipelines are an important tool in oil and gas exploration. Pipeline is a transmission and liquid collection lines, including their accessories, which transport fluids from one plant to another. In transmission and collection process, there is a possibility of failure which can have minor to major impact on personnel injury, the environment and interrupt the business process. To maintain safety and to prevent accidents, the source and cause of failure needs to be calculated. Risk-based inspection (RBI) is a method that can be used to calculate the risk and determine the inspection planning both schedule and method, by combining the probability and consequences of failure. The analysis shows that the production separator is in the low-risk category. The next inspection schedule is determined based on RBI estimation which is 13 years after the last inspection. Inspection methods that can be applied to subsea pipeline based on DNVGL-RP-F116 standard are external inspection, in-line inspection with intelligent pig, and monitoring system. For external inspection can use Remotely Operated Vehicle (ROV). In-line inspection (ILI) with intelligent pig need to validate by with underwater UT B-Scan in the following year. The monitoring system only needs to be continued from what has been installed, corrosion coupon. It only needs to be adjusted for the length of installation time according to its purpose, to measure corrosion rate or detect pitting.